Gold-Catalyzed Synthesis of 2-Substituted Azepanes: Strategic Use of Soft Gold(I) and Hard Gold(III) Catalysts - Morita, Nobuyoshi; Saito, Yuta; Muraji, Ayumi; Ban, Shintaro; Hashimoto, Yoshimitsu; Okamoto, Iwao; Tamura, Osamu (Synlett, 2016)
Strategic use of both soft gold(I) and hard gold(III) catalysts provides azepanes from propargylic alcohols in one pot. Thus, propargylic alcohols in the presence of soft gold(I) catalyst (Ph3PAuNTf2) undergo a Meyer–Schuster rearrangement to give α,β-unsaturated ketones, which in turn undergo a gold(III) (AuBr3)-catalyzed aza-Michael addition to afford azepanes bearing a carbonyl group.
Keywords: soft gold(I) catalyst; hard gold(III) catalyst; azepanes; Meyer–Schuster rearrangement; aza-Michael addition